Peranan Sapta Pesona Dalam Pengembangan Dusun Ngaduman - Yustina Denik Risyanti; Julian Andriani Putri; Tri Maryani (FKIP, Universitas Palangka Raya, 2023)
The elements of Sapta Pesona Wisata are: 1. Safe, 2. Orderly, 3. Clean, 4. Cool, 5. Beautiful, 6. Friendly, 7. Memories. This can be created, among others, by providing comfortable, good and healthy accommodation; dazzling distinctive cultural arts attractions; delicious regional specialties and drinks with attractive presentation and appearance; local souvenirs that are of high quality, easy to carry, affordable and have a special meaning for the places they visit. Promoting and cultivating Sapta Pesona Wisata in everyday life has a much broader objective, namely to increase national discipline and national identity which will also enhance the good image of the nation and state. The large number of tourist objects makes the government pay less attention to tourist objects that are not included in the Priority Tourism Objects. However, developing and managing tourist objects as a whole is one of the government's main tasks in sustainability